Ultrasonic and hydrothermal mediated synthesis routes for functionalized Mg-Al LDH: Comparison study on surface morphology, basic site strength, cyclic sorption efficiency and effectiveness - Ezeh, Collins I.; Tomatis, Marco; Yang, Xiaogang; He, Jun; Sun, Chenggong (Elsevier, 2018)
Amine functionalized layered double hydroxide (LDHs) adsorbents prepared using three different routes: co-precipitation, sono-chemical and ultrasonic-assisted high pressure hydrothermal. The prepared adsorbent samples were characterized using X-ray diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Scanning electron microscope-Energy dispersive X-ray spectroscopy (SEM-EDX), Temperature Programmed Desorption (TPD), Brunauer-Emmett-Teller (BET), and Thermogravimetric analysis (TGA), respectively. The performance of the prepared adsorbents was tested in a controlled thermal-swing adsorption process to measure its adsorption capacity, regeneration and cyclic efficiencies subsequently. The characterisation results were compared with those obtained using the conventional preparation routes but taking into account of the impact of sonochemical and hydrothermal pre-treatment on textural properties, adsorption capacity, regeneration and cyclic efficiencies. Textural results depicts a surge in surface area of the adsorbent synthesised by hydrothermal route (311 m2/g) from 25 to 171 m2/g for conventional and ultrasonic routes respectively. Additionally, it has been revealed from the present study that adsorbents prepared using ultrasonic-assisted hydrothermal route exhibit a better CO2 uptake capacity than that prepared using sonochemical and conventional routes. Thus, the ultrasonic-assisted hydrothermal treatment can effectively promote the adsorption capacity of the adsorbent. This is probably due to the decrease of moderate (M-O) and weak (OH− groups) basic sites with subsequent surge in the number of strong basic sites (O2−) resulting from the hydrothermal process. Moreover, the cyclic adsorption efficiency of the ultrasonic mediated process was found to be 76% compared with 60% for conventional and 53% for hydrothermal routes, respectively. According to the kinetic model analysis, adsorption mechanism is mostly dominated by physisorption before amine modification and by chemisorption after the modification process.